First drug utilization data related to an anticholinergic agent recently marketed in Italy - Lucioni, Carlo; Mazzi, S.; Cerra, C.; Lottaroli, S. (Farmeconomia. Health economics and therapeutic pathways, 2006)
A retrospective drug utilisation study was conducted, concerning a new bronchodilator (tiotropium, ATC code: R03BB04) in the first six months after its launch in Italy. The source of data was the administrative database run by a Local Health Unit located in Northern Italy. All patients (920) were selected with at least one prescription for tiotropium between September and December 2004, and data about their use of health resources (hospitalisations, class ATC R03 drugs, lab tests – only drugs and test prescribed in outpatient setting) was collected. Starting from such initial sample, further sub-samples were created (in particular to focus on patients affected by COPD – Chronic Obstructive Pulmonary Disease, for which tiotropium has got the therapeutic indication by the Italian Health Service), for the purpose of different levels of analysis. Results reported in this abstract are referred to the first level (702 patients, aged 40 years or more, still living at the end of the observation period, already with COPD in the previous year); they are expressed as average data per patient on a six-month period. Prescriptions of R03 drugs were 7.8, including 2.4 specifically for tiotropium. To such prescriptions, 348 and 103 DDDs (Defined Daily Doses) respectively corresponded; and, analogously, a cost of 487 and 205 euros. The cost for hospitalisations was 525 euros and the cost for lab tests was 28.5 euros. The other analysis levels (sub-samples with fewer patients) produced not very different outcomes. Evidence given here should prove the potential interest of such kind of studies.